Drivers for change: Western Australian Patient Blood Management Program (WA PBMP), World Health Assembly (WHA) and Advisory Committee on Blood Safety and Availability (ACBSA) - Farmer, Shannon; Towler, Simon; Leahy, M; Hofmann, A (Elsevier, 2013)
Patient blood management is now high on national and internationalhealth-system agendas. Serious supply challenges as a resultof changing population dynamics, escalating cost of blood, ongoingsafety challenges and questions about transfusion efficacy andoutcomes are necessitating change in transfusion practice.Numerous initiatives are underway to bring about change, includingthe institution of comprehensive patient blood management programmes.In 2008, the Western Australia Department of Healthinitiated a 5-year project to implement a comprehensive healthsystem-wide Patient Blood Management Program with the aim ofimproving patient outcomes while reducing costs. Clinically, theProgram was structured on the three pillars of patient bloodmanagement, namely (1) optimising the patient’s own red cellmass, (2) minimising blood loss and (3) harnessing and optimisingthe patient-specific anaemia reserve. It employs multiple strategiesto bring about a cultural change from a blood-product focus toa patient focus. This Programwas undertaken in a State that alreadyhad one of the lowest red blood cell issuance rates per 1000 populationin the developed world (30.47 red blood cell units per 1000population). The Program identified reasons and drivers for practicechange. From financial years 2008–09 to 2011–12, issuance hasprogressively decreased in Western Australia to 27.54 units per1000. During the same years, despite increasing activity, totalissuance of red blood cells to the entire State decreased from 70,103units to 65,742. Nationally and internationally, other initiatives areunderway to bring about change and implement patient bloodmanagement. The World Health Assembly in May 2010 adoptedresolution WHA63.12 endorsing patient blood management and itsthree-pillar application. The United States Advisory Committee onBlood Safety and Availability met in 2011 to consider the implicationsof this resolution and its implementation.